The Influence of Career Development, Allowances, and Green Behavior on Work Discipline with Organizational Commitment as a Mediating - Nur, Muh.; Herminingsih, Anik (International Journal of Management and Digital Business, 2025)
Purpose – This study aims to examine the effects of career development, allowances, and green behavior on work discipline, with organizational commitment serving as a mediating variable, within the Directorate General of Village and Rural Development, Ministry of Villages and Development of Disadvantaged Regions Methodology/approach – The research employed a proportionate stratified random sampling technique, selecting a sample of 185 employees. Data were collected through questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Findings – It The results reveal that career development, allowances, and green behavior have a positive and significant impact on work discipline. Additionally, organizational commitment significantly mediates the relationships between these independent variables and work discipline. Novelty/value – This study contributes to filling the knowledge gap regarding the role of green behavior in government institutions responsible for sustainable village development. The findings offer practical implications for policymakers to prioritize transparent career development systems, adequate allowances, and the institutionalization of green behavior to strengthen organizational commitment and enhance employee work discipline.